Tumor-Preferential Induction of Immune Responses and Epidermal Cell Death in Actinic Keratoses by Ingenol Mebutate - Emmert, Steffen (PLoS One, 2016)
The rapid and strong clinical efficacy of the first-in-class, ingenol mebutate, against actinic keratosis (AK) has resulted in its recent approval. We conducted the first comprehensive analysis of the cellular and molecular mode of action of topical ingenol mebutate 0.05% gel in both AK and uninvolved skin of 26 patients in a phase I, single-center, open-label, within-patient comparison. As early as 1 day after application, ingenol mebutate induced profound epidermal cell death, along with a strong infiltrate of CD4(+) and CD8(+) T-cells, neutrophils, and macrophages. Endothelial ICAM-1 activation became evident after 2 days. The reaction pattern was significantly more pronounced in AK compared with uninvolved skin, suggesting a tumor-preferential mode of action. Extensive molecular analyses and transcriptomic profiling of mRNAs and microRNAs demonstrated alterations in gene clusters functionally associated with epidermal development, inflammation, innate immunity, and response to wounding. Ingenol mebutate reveals a unique mode of action linking directly to anti-tumoral effects. Trial Registration: ClinicalTrials.gov NCT01387711